Antimicrobial and antiadhesive effects of Lactobacillus isolates of healthy human gut origin on Enterotoxigenic Escherichia coli (ETEC) and Enteroaggregative Escherichia coli (EAEC). (November 2020) - Pazhoohan, Maryam; Sadeghi, Farzin; Moghadami, Morteza; Soltanmoradi, Hossein; Davoodabadi, Abolfazl
Abstract: Purpose: Diarrhea is one of the five leading causes of mortality in children under the age of five, especially in developing countries. Nowadays, by increasing the resistance of pathogens to antibiotics, employment of probiotics as novel therapeutic method, could be considered as a necessity.The aim of this study was to examine the features and antagonistic action of Lactobacillus strains, against the growth and adhesion of Enterotoxigenic Escherichia coli (ETEC) and Enteroaggregative Escherichia coli (EAEC) strains creating diarrhea in children. Then, we introduced new strains of Lactobacillus as probiotic candidates, to prevent diarrheal infections in children. Methods: Stool samples were collected from healthy individuals, and Lactobacillus strains were isolated. The antimicrobial effect of the isolates against ETEC and EAEC strains investigated by agar well diffusion method and their resistance to acidic and bile conditions. The potency of selected isolates in adhesion to HT-29 epithelial cells and their ability to inhibit the adhesion of ETEC and EAEC strains to this cell were measured. At the end, identification of the optimally efficient Lactobacillus isolates was performed by 16S rDNA sequencing and making Phylogenetic tree using MEGA (version 4.0) software. Results: In total, 157 isolates suspected to Lactobacillus were isolated from 115 stool samples. In antimicrobial activity test, ETEC and EAEC growth was inhibited by 132 and 84 isolates respectively, while 17 isolates showed resistance to Bile. Of 17 Bile resistant Lactobacillus isolates, 15 isolates were resistant to pH: 3.2. Further, among 15 isolates, only two isolates, were resistant to pH: 2.5. In the adhesion assay, five isolates had more adhesion tendency to HT-29 epithelial cells than L. rhamnosus GG, which was considered as a positive control. Investigation of isolates that inhibit adhesion of ETEC and EAEC strains to HT-29 cells showed that four isolates were able to inhibit ETEC adhesion. However, only one out of four isolates was relatively able to have an impact on EAEC adhesion. Conclusion: In conclusion, three species of Lactobacillus including L. paracasei (two strain), L . fermentum (two strain) and L. plantarum showed good probiotic properties compared to other isolates that were identified by sequencing. In this study, strain L. fermentum 61.1 had the highest adhesion ability to HT-29 cells and strain L. paracasei 47.2 had the highest potency to inhibit ETEC adhesion to HT-29 cells. These isolates have good probiotic properties and are likely to be effective in preventing or treating diarrheal infections, especially in children. Highlights: Fecal sample of healthy Iranian people is a good origin for native probiotic Lactobacillus strains. Three species of Lactobacillus including L. paracasei (two strain), L. fermentum (two strain) and L. plantarum showed good probiotic properties compared to other isolates that were identified by sequencing. L. fermentum 61.1 had the highest adhesion ability to HT-29 cells and strain L. paracasei 47.2 had the highest potency to inhibit ETEC adhesion to HT-29 cells.